The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1678-58782005000200012
|View full text |Cite
|
Sign up to set email alerts
|

Study on the behavior of the minimum quantity lubricant - MQL technique under different lubricating and cooling conditions when grinding ABNT 4340 steel

Abstract: Energy consumption, air pollution and industrial waste have received special attention from public authorities in recent years. The environment has become one of the most important subjects in the context of modern life, for its deterioration impacts the quality of life populations. Driven by pressure from environmental agencies, politicians have drawn up ever stricter laws aimed at protecting the environment and preserving energy resources. All these factors have led industry, research centers and universitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 4 publications
1
40
0
Order By: Relevance
“…Air in the aerosol provides the cooling function and chip removal, whereas oil provides lubrication and cooling by droplet evaporation. The flow of lubricant in MQL process varies from 10 to 100 ml/h and air pressure varies from 4 to 6.5 Kgf/cm 2 (Silva et al, 2005). Different ranges for flow rate were also reported in literature such as 50 to 500 ml/h (Dhar et al, 2006a) and 2 to 300 ml/h (Zhong et al, 2010).…”
Section: Minimum Quantity Lubricationmentioning
confidence: 91%
“…Air in the aerosol provides the cooling function and chip removal, whereas oil provides lubrication and cooling by droplet evaporation. The flow of lubricant in MQL process varies from 10 to 100 ml/h and air pressure varies from 4 to 6.5 Kgf/cm 2 (Silva et al, 2005). Different ranges for flow rate were also reported in literature such as 50 to 500 ml/h (Dhar et al, 2006a) and 2 to 300 ml/h (Zhong et al, 2010).…”
Section: Minimum Quantity Lubricationmentioning
confidence: 91%
“…Some researchers investigated the effects of grinding parameters on AISI 4340 steel grinding using conventional lubrication and MQL. They found that the surface roughness, diametric wear, grinding forces and residual stress improved when using the latter, due to optimum lubrication of the grinding zone, providing rather grain slipping at www.intechopen.com the contact zone (Silva et al, 2005;Silva et al, 2007). Brunner showed that the MQL grinding with a 4 ml/min ester oil (comparing to 11 ml/min mineral oil), when machining 16MnCr5 (SAE-5115) steel with microcrystalline aluminum oxide reduced the process normal and tangential forces to one third, however increasing the surface roughness by 50% (Tawakoli et al, 2009).…”
Section: Mql In Grindingmentioning
confidence: 99%
“…Hafenbraedl and Malkin found that MQL provides efficient lubrication, reduces the grinding power and the specific energy to a level of performance comparable or superior to that obtained from conventional soluble oil (at a 5% concentration and a 5.3 l/min flow), while at the same time it significantly reduces the grinding wheel wear. However, it presented slightly higher surface roughness values (Ra) (Hafenbraedl & Malkin, 2001;Silva et al, 2005;Silva et al, 2007). The performance was also assessed when applying dry grinding.…”
Section: Mql In Grindingmentioning
confidence: 99%
“…Experimental study on grinding of cast iron by using various nanofluid lubricating mixtures gives positive improvement in surface finish, and G ratio. [4]. Cong Mao et al had reported MQL grinding is more environmental friendly and economic for AISI 52100 steel [5].…”
Section: Introductionmentioning
confidence: 99%